Interactions of Staphylokinase with Human Platelets - Lijnen, H R; Van Hoef, B; Collen, D (Thrombosis and Haemostasis, 1995)
The interactions of recombinant staphylokinase (SakSTAR) with human platelets were investigated in a buffer milieu, in a human plasma milieu in vitro, and in plasma from patients with acute myocardial infarction (AMI) treated with SakSTAR.In a buffer milieu, the activation rate of plasminogen by SakSTAR or streptokinase (SK) was not significantly altered by addition of platelets. Specific binding of SakSTAR or SK to either resting or thrombin- activated platelets was very low. ADP-induced or collagen-induced platelet aggregation in platelet-rich plasma (PRP) was 94 ± 2.7% or 101 ± 1.7% of control in the presence of 0.1 to 20 μM SakSTAR, with corresponding values of 95 ± 2.8% or 90 ± 4.6% of control in the presence of 0.1 to 4 μM SK. No effects were observed on platelet disaggregation. ATP secretion following collagen-induced platelet aggregation was 4.3 ± 0.26 μM for SakSTAR (at concentrations of 0.1 to 20 μM) and 4.4 ± 0.35 μM for SK (at concentrations of 0.1 to 4 μM), as compared to 3.4 ± 0.70 μM in the absence of plasminogen activator.Fifty % lysis in 2 h (C50) of 60 μl 125I-fibrin labeled platelet-poor plasma (PPP) clots prepared from normal plasma or from plasma of patients with Glanzmann thrombasthenia and immersed in 0.5 ml normal plasma, was obtained with 12 or 16 nM SakSTAR and with 49 or 40 nM SK, respectively. C50 values for lysis of 60 μl PRP clots prepared from normal or patient plasma were also comparable for SakSTAR (19 or 21 nM), whereas SK was 2-fold more potent toward PRP clots prepared from Glanzmann plasma as compared to normal plasma (C50 of 130 versus 270 nM).No significant effect of SakSTAR on platelet function was observed in plasma from patients with AMI treated with SakSTAR, as revealed by unaltered platelet count, platelet aggregation and ATP secretion.Thus, no effects of high SakSTAR concentrations were observed on human platelets in vitro, nor of therapeutic SakSTAR concentrations on platelet function in plasma.